Normative data of the Social Connectedness Scale for Argentinean adults - Moran, Valeria (2022)
Social connectedness is a set of cognitions and representations about oneself in relation to others that translates into a feeling of closeness and belonging to the social environment in which the individual is immersed and towards the people who are part of it. The relationship between social connection, mental health and general well-being has been widely evidenced, so its assessment is extremely important in contexts of clinical intervention as well and research. Based on this, the present work aimed to present the normative scores of the Social Connectedness Scale in Argentinean adults and provide classification criteria. The scale was administered to 1305 Argentineans between 18 and 60 years old, and we proposed norms by age, considering that significant differences were found between groups according to this variable. The 25th and 75th percentiles were proposed as classification criteria, indicating low and high social connection, respectively, and these cut-off points presented excellent reliability and good discriminative power.